Communal discord, child abduction and rape in the later Middle Ages - Goldberg, Peter J. P. (The new Middles Ages, 2008)
Alice de Rouclif : an eventful childhood -- William Pottell : stories and storytellers -- Ellen Taliour : gender and the remembrance of times past -- Robert Thewed : the ties of tenure and locality -- Anabilla Wastelyne : the ties of kinship -- Dom. William Marrays : stories and readers -- Alice through the looking glass -- Brewing trouble : the devout widow's tale -- Patriarchy, civic identity and the widow of Doncaster